Kajian Tepung Jagung yang Dipragelatinisasi Dilanjutkan Fermentasi Terhadap Kadar Glukosa Darah Mencit Yang Diinduksi Aloksan - Pratiwi, Rizky Indah; Taufiq, Nurkhaerani; Yanto, Subari; Sukainah, Andi; Putra, Reski Praja (Jurnal Pendidikan Teknologi Pertanian, 2024)
This study aims to determine the effect of modified corn flour through the pragelatinization process followed by Lactic Acid Bacteria (LAB) fermentation on lowering blood sugar levels. This study uses a quantitative description method in the form of experiments by comparing the average value of the mice group given the treatment. he first stage involves mice being grouped into 3 groups, each group contains 7 mice, adapted for 14 days, and measuring blood sugar levels before treatment. The second stage is feeding and treatment for 21 days, standard feed without alloxan injection as a negative control, standard feed with alloxan injection as a positive control, and feed containing modified corn flour through the process of pragelatinization and lactic acid fermentation with alloxan injection as a treatment group. The last stage is the measurement of blood sugar levels on the 21st day. The data analysis techniques used in this study were a normality test and a homogeneity test using IBM SPSS Statistics version 25, followed by a quantitative description in the form of experiments by comparing the mean values of the mice groups given treatment. T he results showed that feed containing modified corn flour through pragelatinization and fermentation of lactic acid bacteria had an effect on reducing blood sugar levels in mice. The group of mice that were given feed containing modified corn flour had lower blood sugar levels compared to the group of mice given standard feed (positive control), obtained at 127 mg/dl with a resulting mice body weight of 23.06 g, and feed consumption of 13.66 g.